THE RELATIONSHIP BETWEEN SCHOOL ADMINISTRATORS' PERCEPTIONS OF PSYCHOLOGICAL EMPOWERMENT AND ORGANIZATIONAL IMAGE - Şenay Sezgin NARTGÜN (Fırat University, 2019)
The image of the organization can be based on the interaction of the i